Plastic collapse load analysis of structures considering Moments and axial force - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana UGM, 1990)
ABSTRAK A procedure for the analysis of plastic collapse load of structures considering moments and axial forces is presented. The method is developed based on the static or lower bound theorem. Essentially, this approach involves the determination of the largest load factor for which a statically admissible and safe distribution of internal forces exists. In linear programming form, it is equivalent to ma ximizing the load factor subject to the conditions of equilibrium and yield. In this formulation, the displacement method is employed to obtain the internal forces influence coefficients. Those coefficients are used to obtain the sets of statically admissible internal forces. By substituting those forces into the yield surface, which is approximated by piece wise linear functions, the problem of plastic collapse load analysis can be cast into linear programming problem. A linear programming solution algorithm so called Phase I-Phase 2 procedure is used to solve the problem. A computer program was prepared for the implementation of the method and a number of numerical examples involving multistory frames and tied arch bridge structures was also considered. Numerical results indicated that the method developed in the present study is found to be accurate, much simpler than the available methods, and is capable of analysing structures with irregular geometry. Key words: plastics collapse